Anthropogenic disturbance homogenizes seagrass fish communities - Josephine C. Iacarella; Emily Adamczyk; Dan Bowen; Lia Chalifour; Aaron Eger; William Heath; Sibylla Helms; Margot Hessing‐Lewis; Brian P. V. Hunt; Andrew MacInnis; Mary I. O'Connor; Clifford L. K. Robinson; et al. (Global Change Biology, 2018)
Anthropogenic activities have led to the biotic homogenization of many ecological communities, yet in coastal systems this phenomenon remains understudied. In particular, activities that locally affect marine habitat‐forming foundation species may perturb habitat and promote species with generalist, opportunistic traits, in turn affecting spatial patterns of biodiversity. Here, we quantified fish diversity in seagrass communities across 89 sites spanning 6° latitude along the Pacific coast of Canada, to test the hypothesis that anthropogenic disturbances homogenize (i.e., lower beta‐diversity) assemblages within coastal ecosystems. We test for patterns of biotic homogenization at sites within different anthropogenic disturbance categories (low, medium, and high) at two spatial scales (within and across regions) using both abundance‐ and incidence‐based beta‐diversity metrics. Our models provide clear evidence that fish communities in high anthropogenic disturbance seagrass areas are homogenized relative to those in low disturbance areas. These results were consistent across within‐region comparisons using abundance‐ and incidence‐based measures of beta‐diversity, and in across‐region comparisons using incidence‐based measures. Physical and biotic characteristics of seagrass meadows also influenced fish beta‐diversity. Biotic habitat characteristics including seagrass biomass and shoot density were more differentiated among high disturbance sites, potentially indicative of a perturbed environment. Indicator species and trait analyses revealed fishes associated with low disturbance sites had characteristics including stenotopy, lower swimming ability, and egg guarding behavior. Our study is the first to show biotic homogenization of fishes across seagrass meadows within areas of relatively high human impact. These results support the importance of targeting conservation efforts in low anthropogenic disturbance areas across land‐ and seascapes, as well as managing anthropogenic impacts in high activity areas.